If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 = -3x + 8 Reorder the terms: 12 + 5x = -3x + 8 Reorder the terms: 12 + 5x = 8 + -3x Solving 12 + 5x = 8 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 12 + 5x + 3x = 8 + -3x + 3x Combine like terms: 5x + 3x = 8x 12 + 8x = 8 + -3x + 3x Combine like terms: -3x + 3x = 0 12 + 8x = 8 + 0 12 + 8x = 8 Add '-12' to each side of the equation. 12 + -12 + 8x = 8 + -12 Combine like terms: 12 + -12 = 0 0 + 8x = 8 + -12 8x = 8 + -12 Combine like terms: 8 + -12 = -4 8x = -4 Divide each side by '8'. x = -0.5 Simplifying x = -0.5
| 8+2m=2m+16 | | 6x^3-20x=0 | | 5.6q-1.1-4.8q=-0.2q-4.8 | | 0.1y=1.5y | | z-1/4-3z/8=z+1/2 | | 2/3+x=5/8 | | 48*48-50*50= | | 2.7a=13.5 | | 5(x-2)+5x=10 | | -8(x+2)=-10 | | y+9=-21 | | 16x+15=8x+10 | | 3x-1=7x-49 | | j+1/3=-6.8 | | (-a^3)(-2a+4a^2)= | | 4(2x-8)=8(x-8) | | 4x+2x+x=12 | | x/3-6=x/2+4 | | 0.2a=48 | | 22x-6-8x=9-16x | | r-12=43 | | v^2=4v+32 | | (5+i)(5-i)= | | x+17.3=4.7 | | Z+81=8z-7 | | 4(a-4)=8a-(4a-16) | | -81=26+n | | -3=z | | t+2/3+5t/6=4t-5/12 | | -4y+2=-5y+9 | | (-a^3)x(-2a+4a^2)= | | 2b-b-10=-13 |